PENGARUH ZONASI DAN SIRKULASI TERHADAP KEPUASA PELANGGAN DAN KINERJA BISNIS pada COSPLAY CENTER DI KOTA MEDAN - Siregar, Mona Hatorangan; Aritonang, Liesbeth (LPPM ISTP, 2025)
Since the Covid Pandemic has been experienced together by all countries in various parts of the Continent, various activities and events have begun to emerge, communities of young people and adults who are stuck in their respective rooms can finally gather and socialize directly again, one of the communities that has caught the author's attention is the Cosplay Community, especially in the city of Medan. The Cosplay Community, (derived from the words Costume and Play), is a popular trend where people, both young and old, imitate fictional characters from Anime, Manga (comics), video games, films and so on. In addition, according to PRNewswire, the cosplay costume market size is expected to grow by USD 1,667.34 million from 2022 to 2027. The market growth momentum will increase at a CAGR of 6.26% during the forecast period. APAC is expected to control 75% of the global market during the forecast period. therefore the author designed a facility that can accommodate various activities, retail, training places and a special area